2017
DOI: 10.1017/s1047951117001469
|View full text |Cite
|
Sign up to set email alerts
|

Filling a significant gap in the cardiac ICU: implementation of individualised developmental care

Abstract: Mortality rates among children with CHD have significantly declined, although the incidence of neurological abnormalities and neurodevelopmental impairment has increased. Research has focussed on outcomes, with limited attention on prevention and intervention. Although some developmental differences and challenges seen in children with CHD are explained by the cumulative effect of medical complications associated with CHD, many sequelae are not easily explained by medical complications alone. Although cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 44 publications
(69 reference statements)
0
41
0
Order By: Relevance
“…5 Individualised developmental care approaches have been well established in neonatal ICUs with preterm infants, 45,46 and this approach is now being introduced in cardiac ICUs around the world. 26,47,48 Similarities in clinical vulnerability associated with neurological dysmaturation and intervention requirements demand a similar focus to minimise risk associated with environmental and care practices on long-term neurodevelopment. 26 Implementing routine pre-operative assessment is valuable; 49 however, it presents challenges with critically unwell infants, 25,50 particularly when interventions such as intubation preclude the handling required for administering assessments.…”
Section: Discussionmentioning
confidence: 99%
“…5 Individualised developmental care approaches have been well established in neonatal ICUs with preterm infants, 45,46 and this approach is now being introduced in cardiac ICUs around the world. 26,47,48 Similarities in clinical vulnerability associated with neurological dysmaturation and intervention requirements demand a similar focus to minimise risk associated with environmental and care practices on long-term neurodevelopment. 26 Implementing routine pre-operative assessment is valuable; 49 however, it presents challenges with critically unwell infants, 25,50 particularly when interventions such as intubation preclude the handling required for administering assessments.…”
Section: Discussionmentioning
confidence: 99%
“…12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants. 12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on neurodevelopment in infancy is relatively new to cardiology, though common for other medical conditions affecting newborns such as preterm birth or fetal abstinence syndrome. 12,35 Research demonstrates that individualized developmental care and other rehabilitative and developmental therapies initiated early in the hospital stay improve long-term outcomes for hospitalized infants. 36 A recent survey found that only a minority of CICUs caring for children with CHD employ consistent developmental rounds, engage in individualized developmental care, and begin therapeutic services such as physical therapy, occupational therapy, speech and language therapy, feeding therapy, and child life therapy early in the hospital stay, indicating the focus on neurodevelopment is still evolving in cardiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder of the article will focus on an area that has not received as much attention in this population: provision of developmentally supportive care. Developmentally supportive care refers to interventions that are individualized to the infant's needs and focused on minimizing infant stress response to optimize brain development (Butler, Huyler, Kaza, & Rachwal, 2017;Peterson & Evangelista, 2017;Sood et al, 2016). The brain maturity of term-born infants with CCHD is often similar to that of infants born prematurely at 34-35 weeks, and infants with CCHD have adverse neurodevelopmental outcomes similar to infants born prematurely (Andropoulos et al, 2010;Calderon & Bellinger, 2015;Compas, Jaser, Reeslund, Patel, & Yarboi, 2017;Licht et al, 2009).…”
Section: Congenital Heart Diseasementioning
confidence: 99%